2003
DOI: 10.1523/jneurosci.23-35-11045.2003
|View full text |Cite
|
Sign up to set email alerts
|

The β3 Nicotinic Receptor Subunit: A Component of α-Conotoxin MII-Binding Nicotinic Acetylcholine Receptors that Modulate Dopamine Release and Related Behaviors

Abstract: Nigrostriatal dopaminergic neurons express many nicotinic acetylcholine receptor (nAChR) subunits capable of forming multiple nAChR subtypes. These subtypes are expressed differentially along the neuron and presumably mediate diverse responses. beta3 subunit mRNA has restricted expression but is abundant in the substantia nigra and ventral tegmental areas. To investigate the potential role(s) of nicotinic receptors containing the beta3 subunit in dopaminergic tracts, we generated mice with a null mutation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
195
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(212 citation statements)
references
References 46 publications
14
195
1
2
Order By: Relevance
“…These properties of naturally occurring α4β2 receptors could explain the discrepancy between binding and function seen in the α5 subunit null mutant mouse where high affinity (α4β2*) binding appears unchanged but the high affinity function is decreased. (Figure 3) or in a detectable change in brain mRNA concentrations for any of the other subunits (α2-α7, β2, β4) that are normally expressed in mouse brain [100]. Thus, β3 gene deletion elicited an increase in a response that appears to be modulated by α4(α5)β2 nAChRs, but it did not change the number of receptors that are measured by a binding assay that requires expression of α4 and β2 subunits.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…These properties of naturally occurring α4β2 receptors could explain the discrepancy between binding and function seen in the α5 subunit null mutant mouse where high affinity (α4β2*) binding appears unchanged but the high affinity function is decreased. (Figure 3) or in a detectable change in brain mRNA concentrations for any of the other subunits (α2-α7, β2, β4) that are normally expressed in mouse brain [100]. Thus, β3 gene deletion elicited an increase in a response that appears to be modulated by α4(α5)β2 nAChRs, but it did not change the number of receptors that are measured by a binding assay that requires expression of α4 and β2 subunits.…”
mentioning
confidence: 84%
“…Deleting the β3 gene resulted in an unexpected increase in the αCtxMII-resistant component of ACh-stimulated dopamine release. This increase was not accompanied by a discernable change in cytisine-sensitive [ 3 H]-epibatidine binding (Figure 3) or in a detectable change in brain mRNA concentrations for any of the other subunits (α2-α7, β2, β4) that are normally expressed in mouse brain [100]. Thus, β3 gene deletion elicited an increase in a response that appears to be modulated by α4(α5)β2 nAChRs, but it did not change the number of receptors that are measured by a binding assay that requires expression of α4 and β2 subunits.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Results from a comprehensive molecular genetics study in which an individual subunit gene (i.e., α4, α5, α7, β2, β3, and β4) was deleted suggested that at least 6 different subtypes mediate nicotine-evoked DA release from mouse striatal synaptosomes, including 2 classes of nAChRs: α-CtxMII-sensitive nAChRs (i.e., α6β2β3*, α4α6β2β3* and possibly a small amount of α6β2* or α4α6β2* subtypes) and α-CtxMIIresistant nAChRs (i.e., α4β2* and α4α5β2* subtypes), whereas deletion of β4 and α7 subunits had no effect [39]. Also, α6-and β3-containing nAChRs have been implicated in nicotineevoked DA release [24,40,41]. Additionally, substantia nigra neurons express high levels of both α6 and β3 mRNA [26,[40][41][42][43] consistent with their involvement in mediating nicotineevoked DA release.…”
Section: Introductionmentioning
confidence: 98%
“…Also, α6-and β3-containing nAChRs have been implicated in nicotineevoked DA release [24,40,41]. Additionally, substantia nigra neurons express high levels of both α6 and β3 mRNA [26,[40][41][42][43] consistent with their involvement in mediating nicotineevoked DA release.…”
Section: Introductionmentioning
confidence: 99%